2018
DOI: 10.1016/j.redox.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidasin-mediated crosslinking of collagen IV is independent of NADPH oxidases

Abstract: Collagen IV is a major component of the basement membrane in epithelial tissues. The NC1 domains of collagen IV protomers are covalently linked together through sulfilimine bonds, the formation of which is catalyzed by peroxidasin. Although hydrogen peroxide is essential for this reaction, the exact source of the oxidant remains elusive. Members of the NOX/DUOX NADPH oxidase family are specifically devoted to the production of superoxide and hydrogen peroxide. Our aim in this study was to find out if NADPH oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…11,34 Crucial to the stable formation of these bonds are sulfilamine bonds, and these are catalyzed in a peroxidase reaction by peroxidasin, or PXDN. 35 This may explain why the phenotype associated with PXDN may be so severe, as demonstrated in case 21 (Fig. 2c) of this study, and as shown in the mouse pxdn nonsense variant model.…”
Section: Variants In Collagen and Extracellular Matrix-associated Gensupporting
confidence: 60%
“…11,34 Crucial to the stable formation of these bonds are sulfilamine bonds, and these are catalyzed in a peroxidase reaction by peroxidasin, or PXDN. 35 This may explain why the phenotype associated with PXDN may be so severe, as demonstrated in case 21 (Fig. 2c) of this study, and as shown in the mouse pxdn nonsense variant model.…”
Section: Variants In Collagen and Extracellular Matrix-associated Gensupporting
confidence: 60%
“…Such PXDN functions require both the ECM motifs and peroxidase activity, which can be blocked by anti-PXDN antibody and peroxidase inhibitor by NOX enzymes. 4,27 The low enzymatic activity of PXDN led to the hypothesis that the PXDN in myofibroblasts is involved in a novel ECM-formation pathway that is not mediated by peroxidase activity. 7 Our study showed, however, that PXDN functions extracellularly as a secreted protein and that its functional loss in ECs is driven by deletions of the peroxidase domain or by peroxidase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the level of NC1 domain sulfilimine crosslinking in Col IV according to a procedure reported previously [32]. Briefly, the lung tissues were lysed in hypotonic lysis buffer (10 mM CaCl 2 , 50 mM HEPES, pH 7.4, 0.1 mM benzamininde hydrochloride, 25 mM 6-aminocaproic acid, and 1 mM PMSF).…”
Section: Detection Of Nc1 Sulfilimine Crosslinkmentioning
confidence: 99%